2017
DOI: 10.1523/jneurosci.3816-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pain Reduces C Fiber Activity-Dependent Slowing in a Sex-Dependent Manner, Amplifying Nociceptive Input to the Spinal Cord

Abstract: C fibers display activity-dependent slowing (ADS), whereby repetitive stimulation (≥1 Hz) results in a progressive slowing of action potential conduction velocity, which manifests as a progressive increase in response latency. However, the impact of ADS on spinal pain processing has not been explored, nor whether ADS is altered in inflammatory pain conditions. To investigate, compound action potentials were made, from dorsal roots isolated from rats with or without complete Freund's adjuvant (CFA) hindpaw infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 97 publications
4
21
1
Order By: Relevance
“…Here, we demonstrate that in peripheral nerve tissue from paclitaxel‐treated rats, C‐fibres had significantly lower ADS, an effect that was prevented in those rats co‐treated with melatonin. We have very recently reported that C‐fibre ADS alters the temporal relay of pain input to the spinal cord and that a reduction in ADS, as we have observed in the paclitaxel model, facilitates central pain processing, and likely contributes to pain hypersensitivity …”
Section: Discussionsupporting
confidence: 52%
“…Here, we demonstrate that in peripheral nerve tissue from paclitaxel‐treated rats, C‐fibres had significantly lower ADS, an effect that was prevented in those rats co‐treated with melatonin. We have very recently reported that C‐fibre ADS alters the temporal relay of pain input to the spinal cord and that a reduction in ADS, as we have observed in the paclitaxel model, facilitates central pain processing, and likely contributes to pain hypersensitivity …”
Section: Discussionsupporting
confidence: 52%
“…For those involving SP neurons, we used Tac1 Cre mice that had received intraspinal injection of either AAV.flex.eGFP or AAV.flex.tdTom between 1 and 3 weeks previously. Spinal cord slices were obtained from 40 injected Tac1 Cre mice and from 105 GRP::eGFP mice aged 4 to 10 weeks old, as described previously [14,34]. The spinal cord was removed either following laminectomy performed under isoflurane anaesthesia, or in ice-cold dissection solution after decapitation of the mice under brief isoflurane or tribromoethanol anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Mice from which the cord was removed under anaesthesia were decapitated immediately afterwards. Parasagittal (300 – 500 μm), transverse (400 – 600 μm) or horizontal (400 μm) slices from lumbar spinal cord were cut with a vibrating blade microtome and allowed to recover in recording or modified dissection solution for at least 30 minutes at room temperature [14,34]. In some cases the slices were placed in a NaCl-based recovery solution or an N -methyl-D-glucamine (NMDG) -based recovery solution [64] at 32°C for 15 minutes before being placed in recording solution at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This is compounded by epigenetic modifications in humans and by the limited ability of rodent models to predict clinical efficacy (Mogil, 2017;Patel et al, 2017;Sexton et al, 2017;Yekkirala et al, 2017). Despite the realization that pain processing in males differs from that in females (Mogil, 2012b;Mifflin and Kerr, 2013;Sorge et al, 2015;Dodds et al, 2016;Melchior et al, 2016;Dickie et al, 2017;Sorge and Totsch, 2017), many preclinical studies have been done on male rodents to avoid possible complications imposed by the estrous cycle. It is also established that neonatal injury can affect manifestation of pain in adults (Beggs et al, 2012a).…”
Section: A Clinical Presentation and Pharmacotherapy Of Neuropathicmentioning
confidence: 99%